Reputation, Responsibility, and Stakeholder Support in Scandinavian Firms: A Comparative Analysis - Vidaver-Cohen, Deborah (Journal of business ethics, 2015)
This paper describes an exploratory study of corporate responsibility, corporate reputation, and stakeholder support in Norway, Sweden and Denmark—countries recognized worldwide as providing an institutional climate uniquely conducive to responsible business practice. Conducting a secondary analysis of Scandinavian data from Reputation Institute’s extensive global research on corporate reputation and responsibility, we examine four key questions: First, do Scandinavians agree with external observers that firms in their countries demonstrate superior levels of corporate responsibility? Second, relative to other reputation drivers, to what extent does corporate responsibility predict corporate reputation for the countries in our dataset? Third, to what extent does corporate responsibility predict stakeholder intent in these countries to engage in supportive behavior toward the firm? Finally, are stakeholder perceptions of and responses to corporate responsibility sufficiently similar across Norway, Sweden, and Denmark to justify claims for a monolithic “Scandinavian approach” to CSR? Previous research examining the relationship of corporate responsibility to corporate reputation and stakeholder support is reviewed, analytical methods are described, results presented, and implications discussed. The article concludes with analysis of study limitations and directions for future research.